Sss-class revival hunter. 03 - Sinnoa; Neida (Sss-Class Revival Hunter, 2025)
Leading an army to victory is a piece of cake for someone with the right skillset, like Gongja! Following their success, the top ten ranked hunters are unexpectedly summoned to a different place to choose between rewards from the goddess and the Demon King. However, Gongja's got more urgent things to take care of. A gathering of the top hunters means facing the Sword Emperor, so forget making the right choice-will Gongja manage to get out of this alive?